AN ANALYSIS OF MOSQUES WEDDING CEREMONIES IN METROPOLITAN KANO STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
The spatio-temporal documentation and researches related to changes pertaining the cultural processes such as landscape, naming and wedding ceremonies among Hausa ethnicity of Kano State is lacking and grossly inadequate. The study aimed at ascertaining the state of wedding ceremonies in Kano state. Identification of major changes temporally, causes of the changes and the consequential implication were unveiled. Five local government areas were sampled randomly with twenty respondents in each for the study. Interview is used as instrument for data collection. The data obtained were analyzed using Simple statistical tool. The study revealed that, the rate of changes in wedding ceremonies is higher in the urban space presently than ever in the history of the areas like that of naming ceremony. Packing space, convenience, Sectarianism, socio-economic status, breakage of extended family are among the causes of the changes. The family ties and relationship that such gathering promote among the community and family members are threatened. Wedding and naming at mosques overtake house-frontages with high magnitude. The cultural and socio-economic impact of home based ceremonies are lost such as inter personal contact, exchange of gifts, transactions and feeding of the needy alleviating poverty. Culture turn is needed in areas of ceremonies among the community as revealed bythe study. The study recommends that, coherent attitudes unity and participations should be encouraged by the community elders. Public-Private partnership should be encouraged towards developing naming ceremonies as cultural heritage in order to diversify the economy of Kano.
Keywords: Weeding, poverty, Religion, Culture, Community